Factors of Halal Industry Ecosystem Development: A Study on the Islamic Hospital Industry in Indonesia - Masruroh, Aini; Rahmawati, Yuke (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2025)
Research Originality: This study offers originality by examining Islamic hospitals, a sector that has been rarely explored in halal industry research. It employs a quantitative approach to analyze how knowledge and perception influence public intention, with preference serving as a mediating variable, providing new empirical evidence for strengthening the halal ecosystem in healthcare services. Research Objectives: This study aims to investigate the impact of knowledge and perception factors on public intentions to use sharia-certified hospitals, with preference serving as a mediating variable. Research Method: A quantitative descriptive approach was employed, utilizing primary data collected through questionnaires and analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. Respondents consisted of individuals living in areas with the presence of Islamic hospitals. Empirical Results: The results showed that knowledge and perceptions have a significant influence on community preferences. Perceptions and preferences are also proven to affect people's intentions in choosing Islamic hospitals, while knowledge does not show a direct impact on intentions. Preference acts as a mediator in the relationship between knowledge, perception, and intentions. Implications: The findings underscore the significance of education in enhancing public knowledge, promoting positive perceptions, and developing effective marketing and regulatory strategies to strengthen the position of Islamic hospitals within the halal ecosystem development in Indonesia. JEL Classification: M31, O14, Z12 How to Cite:Masruroh, A., & Rahmawati, Y. (2025). Factors of Halal Industry Ecosystem Development: A Study on the Islamic Hospital Industry in Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 14(2), 591-604. https://doi.org/10.15408/sjie.v14i2.46428.